Prophylactic Admission of an In Vitro Reconstructed Complexes of Human Recombinant Heat Shock Proteins and Melanoma Antigenic Peptides Activates Anti-Melanoma Responses in Mice - V. Savvateeva, L.; M. Schwartz, A.; B. Gorshkova, L.; V. Gorokhovets, N.; A. Makarov, V.; P. Reddy, V.; Aliev, G.; A. Zamyatnin, A. (Current Molecular Medicine, 2015)
Tumor-derived autologous antigenic peptides when bound to endogenous 70 kDa family heat shock proteins (HSP70) are able to induce effective T-cell responses against tumors. However, efficacy of HSPbased vaccines in clinical practical stand point still has a number of certain limitations including an activation of immune responses against alien non-human HSPs. In this study we reconstructed the complexes of human recombinant HSPs70 (human recombinant HSP70A1B and HSC70 mixture; hrHSPs70) with antigenic lowweight peptides derived from mice B16F10 melanoma cell lysate (PepMCL) in vitro and investigated the prophylactic potential of these complexes to activate anti-tumor immunity in melanoma mouse model. Our results demonstrate that the developed prophylactic vaccine elicits melanoma-specific immune responses and anti-tumor effects against melanoma. These results suggest that hrHSPs70 has capability to reconstitute complexes with peptides obtained from tumor cells lysates in vitro and, therefore, can be used for delivery of multiple antigenic peptides into antigen-presenting cells (APCs) to activate effectors cells. Designed in such a way hrHSPs70-based prophylactic vaccines induce immune responses resulting in a significant efficient prevention of tumor growth and metastases.
Keywords: Hsp70